Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2004
DOI: 10.1063/1.1806531
|View full text |Cite
|
Sign up to set email alerts
|

Infrared absorption from OH− ions adjacent to lithium acceptors in hydrothermally grown ZnO

Abstract: An intense infrared absorption band has been observed in a hydrothermally grown ZnO crystal. At 12K, the band peaks near 3577.3cm−1 and has a half width of 0.40cm−1, and at 300K, the band peaks at 3547cm−1 and has a half width of 41.3cm−1. This absorption band is highly polarized, with its maximum intensity occurring when the electric field of the measuring light is parallel to the c axis of the crystal. Photoinduced electron-paramagnetic-resonance experiments show that the crystal contains lithium acceptors (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
47
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(53 citation statements)
references
References 47 publications
5
47
1
Order By: Relevance
“…H can act as a shallow donor [2][3][4] or indirectly contribute to n-type activity by passivating compensating acceptors. 5 Li, on the other hand, behaves as an amphoteric impurity, being a donor on an interstitial site (Li i ) and an acceptor on Zn-site (Li Zn ). 5 The relative abundance of Li i and Li Zn depends on the Fermi-level position and the detailed ZnO stoichiometry.…”
Section: Introductionmentioning
confidence: 99%
“…H can act as a shallow donor [2][3][4] or indirectly contribute to n-type activity by passivating compensating acceptors. 5 Li, on the other hand, behaves as an amphoteric impurity, being a donor on an interstitial site (Li i ) and an acceptor on Zn-site (Li Zn ). 5 The relative abundance of Li i and Li Zn depends on the Fermi-level position and the detailed ZnO stoichiometry.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogen is a common impurity in ZnO that strongly influences the electrical and optical properties via formation of defect complexes with impurities and native defects [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…3 The variation in absorption strength is directly related to the variation in concentration of the complex: In an attempt to estimate the absorption strength of the OH-Li complex, it is assumed that all of the Li in wafer E contributes to the OH-Li complex. Then a minimum value of 9.3 9 10 À18 cm is obtained for 3577 .…”
Section: LImentioning
confidence: 99%
“…In HT-ZnO, the dominating OH-related absorption line 4 at 3577 cm À1 is due to a stretch mode of a OHbond in the vicinity of Li on a Zn-site (Li Zn ). 3,5 Halliburton et al 3 found from combined FTIR and electron paramagnetic resonance measurements that 99% of the Li in their samples was contributing to the 3577 cm À1 line, i.e., in other words, passivated by H. It is well known that the Li concentration can vary between different as-grown HT-ZnO wafers, and a correlated variation in the integrated absorption coefficient of the 3577 cm À1 line may thus be expected. A remarkable feature of the OH-Li complex is the high thermal stability, as it has been reported to be stable at 1200°C during several hours.…”
mentioning
confidence: 99%